Anti-Asthmatic and Immunomodulatory Effect of Actinidia deliciosa Fruit on Swiss Albino Mice - Sanjita Das1, Saumya Das2 Sakshi Pal1
The aim of the current research is the evaluation of immunomodulatory and anti-asthmatic activity of Actinidia deliciosa on Swiss albino mice by using a number of experimental models. Materials and Methods: The immunomodulatory and anti-asthmatic activity of Actinidia deliciosa in Swiss albino mice was evaluate by using models like delayed type hypersensitivity, neutrophil adhesion test, milk induced neutrophil leucocytes in mice, clonidine induced catalepsy activity in mice, clonidine induced mast cell degranulation method. Microscopic and histopathology images also taken during the experiment for better analysis of the outcomes. Results: The result obtained after performing the various models were observed that ethanolic extract of fruit of Actinidia deliciosa significantly **p<0.001 inhibit delayed type hypersensitivity, helps to increase neutrophil migration towards foreign body which are primary mediators and playsimportant role to fight infections, it also reduces leucocytes and eosinophilia count increased by milk, hence, work as anti-asthmatic agent. It was also found that the Actinidia deliciosa fruit extract reduces cataleptic activity of mice and protects mast cells from degranulation. Conclusion: The current study findings showed that ethanolic extract of Actinidia deliciosa fruits possess immunomodulatory and anti-asthmatic activity by reducing hypersensitivity reactions, increasing neutrophil migration towards antigens, reduces leucocytes and eosinophilia counts, also helps in the reduction of cataleptogenic activity and protects mass cell degranulation